"Lepet": Indonesian traditional food for Eid Al-Fitr celebrations - Ata Aditya Wardana; R. Haryo Bimo Setiarto; Laras Putri Wigati (Journal of Ethnic Foods, 2023)
Abstract Indonesia, a country with diverse cultures, possesses a rich variety of cultural heritage. The aim of this review is to discuss the culture of lepet considering its ethnic perspective, preparation and consumption, nutritional and functional properties, safety, and future outlook aspects. Lepet, a traditional Javanese dish, consists of sticky rice, grated young coconut, coconut milk, cowpea, and salt. It is wrapped in young coconut leaves with a specific pattern, boiled, soaked, and then hung to cool and dry. The persuasive technique employed by Sunan Kalijaga, which combines Javanese cultural traditions and Islamic religious teachings, symbolizes lepet for the Javanese people. This method facilitated the spread of Islam by emphasizing the importance of purity and refraining from committing further mistakes after apologizing during the Eid Al-Fitri tradition. Lepet is rich in carbohydrates and some protein. It is gluten-free and offers benefits for bone and skin health due to its contribution of antioxidants, vitamins, and minerals. Proper handling and storage of lepet are vital to prevent the growth of harmful bacteria and extend its shelf life. Given the rising worldwide acknowledgment of Indonesian gastronomy, advancements in technology and distribution, creative adaptations, and a surging demand for convenience, the prospects for lepet appear bright in the future.